2016
DOI: 10.1108/ijcst-11-2015-0128
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of females’ preferences for buttock shapes with different ethnic backgrounds

Abstract: Purpose Understanding costumer requirements is a precondition for clothing design and manufacturing. A good shapewear designer should know women’s preferences for their buttock shapes before making patterns. The purpose of this paper is to figure out factors affecting the beauty of women’s buttock shapes and the effect of ethnic background to buttock shapes preference. Design/methodology/approach The approach utilized both 3D virtual models and 3D printed models to detect women’s preference for their buttock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…In order to reduce the inconvenience of multiple parameters for subsequent processing, it was necessary to reduce the dimension before the clustering analysis. 29 First of all, principal component analysis was carried out between 17 variables (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) in Table 2, which were related to shape classification, and the initial solution for factor analysis could be obtained. It was found that the correlation between CA UA and other variables was not strong.…”
Section: Analysis Of Shape Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to reduce the inconvenience of multiple parameters for subsequent processing, it was necessary to reduce the dimension before the clustering analysis. 29 First of all, principal component analysis was carried out between 17 variables (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) in Table 2, which were related to shape classification, and the initial solution for factor analysis could be obtained. It was found that the correlation between CA UA and other variables was not strong.…”
Section: Analysis Of Shape Factorsmentioning
confidence: 99%
“…This method would provide a basis for rapid personalized customization and have very important practical significance. 25…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lia et al (2016) summarized the style preferences for men’s clothing in Hong Kong and classified them according to fashion and masculine, low functional value, covering, and comfort, which all have their own requirements for costume design. Yao et al (2016) compared women of different races’ preferences for hip shapes and discovered that there was a correlation between race and hip shape preferences among women. Nam-Jin and Keum-Hee (2016) classified women’s fashion lifestyles and proposed women’s color preferences in Spring and Summer based on this classification.…”
Section: Introductionmentioning
confidence: 99%
“…Lia et al (2016) summarized and classified the clothing preferences of the Hong Kong men. Yao et al (2016) compared the preferences of women of different races for the hip shapes of clothing. Nam-Jin and Keum-Hee (2016) sorted the fashion life styles of women consumers, based on which they presented women's color preferences in Spring and Summer.…”
Section: Introductionmentioning
confidence: 99%